Gender Criticism in the Azerbaijani Turkic Folktale of the Book of Dede Korkut (ENTHYMEMA, 2022)
Folktale is the mirror of human being society that reflects the people’s ways of life. Among the literary genres, the Azerbaijani folktales play a significant role in the Turkic-speaking communities. The Book of Dede Korkut is one of the oldest folktales of Turkic people. Additionally, gender equality is one of the most significant parts of the stories of the Book of Dede Korkut. Furthermore, men and women have prideful roles in their tribe, and the positions of women, are considered equal to men. This study intends to examine gender role models criticism in the Azerbaijani folktale of the Book of Dede Korkut. This research uses Copenhaver’s theoretical frameworks, such as Behavior Characteristics and Source of Power, to criticize gender role models in the different stories of the Book of Dede Korkut. Thus, this research revealed that there was a significant positive relationship between both genders in their society.
Keywords: Azerbaijani Folktale; Dede Korkut; Gender Criticism; Gender; Copenhaver